Defect‐Induced Pt–Co–Se Coordinated Sites with Highly Asymmetrical Electronic Distribution for Boosting Oxygen‐Involving Electrocatalysis. Issue 4 (28th November 2018) - Zhuang, Linzhou; Jia, Yi; Liu, Hongli; Wang, Xin; Hocking, Rosalie K.; Liu, Hongwei; Chen, Jun; Ge, Lei; Zhang, Longzhou; Li, Mengran; Dong, Chung‐Li; Huang, Yu‐Cheng; et al.
Abstract: Rational design and synthesis of hetero‐coordinated moieties at the atomic scale can significantly raise the performance of the catalyst and obtain mechanistic insight into the oxygen‐involving electrocatalysis. Here, a facile plasma‐photochemical strategy is applied to construct atomically coordinated Pt–Co–Se moieties in defective CoSe2 (CoSe2− x ) through filling the plasma‐created Se vacancies in CoSe2− x with single Pt atomic species (CoSe2− x ‐Pt) under ultraviolet irradiation. The filling of single Pt can remarkably enhance the oxygen evolution reaction (OER) activity of CoSe2 . Optimal OER specific activity is achieved with a Pt content of 2.25 wt% in CoSe2− x ‐Pt, exceeding that of CoSe2− x by a factor of 9. CoSe2− x ‐Pt shows much better OER performance than CoSe2− x filled with single Ni and even Ru atomic species (CoSe2− x ‐Ni and CoSe2− x ‐Ru). Noticeably, it is general that Pt is not a good OER catalyst but Ru is; thus the design of active sites for electrocatalysis at an atomic level should follow a different intrinsic mechanism. Mechanism studies unravel that the single Pt can induce much higher electronic distribution asymmetry degree than both single Ni and Ru, and benefit the interaction between the Co sites and adsorbates (OH*, O*, and OOH*) during the OER process, leading to a better OER activity. Abstract : Atomically coordinated Pt–Co–Se moieties are generated by filling Se vacancies in defective CoSe2 with single Pt atoms (CoSe2− x ‐Pt) under ultraviolet irradiation. Even though Pt is not a good oxygen evolution reaction (OER) catalyst, single Pt can induce a higher electronic distribution asymmetry degree than single Ni and Ru, and benefit the interaction between Co sites and adsorbates, endowing CoSe2− x ‐Pt with much better OER performance.